Efficiency and Performance Stability Analysis of Nominated Suppliers in the Automotive Industry Using a Time-Series Data Envelopment Analysis Approach - Diasj Muhamad Ilyasa Saputra Hidayat; Sukanta (Jurnal Serambi Engineering, 2026)
Supplier management in the automotive industry often faces the dilemma of nominated suppliers, where suppliers are directly appointed by the Original Equipment Manufacturer (OEM), thereby limiting the company's bargaining power in ensuring operational efficiency. This study aims to analyze the technical efficiency and performance stability of 25 nominated suppliers at PT XYZ throughout 2025. The methodology employed is Data Envelopment Analysis (DEA) with the BCC model, input-oriented, and a monthly time-series approach, resulting in a total of 300 Decision Making Unit (DMU) observations. Input variables include Turnaround Time (TAT) and Price Index, while output variables consist of Delivery Rate, Quality Rate, and Response Rate. The results indicate significant fluctuations in technical efficiency scores across all suppliers, with no single supplier capable of maintaining a perfect efficiency level (1.00) consistently throughout the observation period. Slack analysis reveals that the dominant source of inefficiency is caused by TAT durations that exceed peer group reference benchmarks. These findings provide strategic implications for company management to implement a quantitative data-driven early warning system to mitigate late delivery risks and optimize coordination with OEMs.